2006
DOI: 10.1007/s00056-006-5043-2
|View full text |Cite
|
Sign up to set email alerts
|

Die Ausrotation von Prämolaren und Eckzähnen mit NiTi-Elementen

Abstract: In this investigation, a derotation moment of 12 Nmm occurred in the canine with a 140 degrees archwire rotation and a force in lingual direction. This archwire also made overcorrection possible, since it remains active after complete derotation. A complete derotation of the tooth was effected with no reactivation, due to the wire's superelasticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 2 publications
3
14
0
1
Order By: Relevance
“…A root surface of 220 mm 2 is specified for tooth 25 [37]. Accordingly, the appropriate torque for tooth 25 is around 15.8 Nmm, which is consistent with that reported by Sander et al [38] who measured torque during rotation of premolars and canines.…”
Section: Discussionsupporting
confidence: 69%
“…A root surface of 220 mm 2 is specified for tooth 25 [37]. Accordingly, the appropriate torque for tooth 25 is around 15.8 Nmm, which is consistent with that reported by Sander et al [38] who measured torque during rotation of premolars and canines.…”
Section: Discussionsupporting
confidence: 69%
“…Torque of 30 Nmm [41] referred to a molar with an average root surface of about 430 mm 2 [42]. Tooth 25 has a root surface of 220 mm 2 [42], thus the appropriate torque is 10.5 -15.8 Nmm, as reported by Sander et al [43].…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23][24] MTBs with different brush head designs are still used most frequently today. 25,26 Despite extensive research, only one study could be found that could prove the superiority of a manual toothbrush over various electric toothbrushes. 27 ETBs often have the advantage that their brush head is small enough to clean areas that cannot be reached by toothbrushes with larger heads.…”
Section: Toothbrushesmentioning
confidence: 99%
“…Using an ETB is easier for many people to learn than using a MTB. 25,29 Interdental Brushes (IDB) are small brushes for cleaning the interdental space or the space between brackets, when instructed in between them, consisting of a wire core with nylon bristles arranged at an angle of 90°. IDBs with large diameters are particularly suitable for cleaning MBA.…”
Section: Toothbrushesmentioning
confidence: 99%